Janus's Gaze : Essays on Carl Schmitt - Galli, Carlo (Book collections on Project MUSE., 2015)
Appearing here in English for the first time, Janus's Gaze is the culmination of Carlo Galli's ongoing critique of the work of Carl Schmitt where he finds the unifying thread of Schmitt's work to be his creation of the genealogy of modernity.